APPROXIMATION OF FUNCTIONS DEFINED ON THE REAL AXIS BY OPERATORS GENERATED BY λ-METHODS OF SUMMATION OF THEIR FOURIER INTEGRALS - Kharkevych, Yurii I.; Zhyhallo, Tetiana V.; Харкевич, Юрій Іліодорович; Жигалло, Тетяна Василівна (Ukrainian Mathematical Journal, 2004)
We obtain asymptotic equalities for upper bounds of the deviations of operators generated by λ- methods (defined by a collection Λ = {λσ ( ⋅)} of functions continuous on [0; ∞) and depending on a real parameter σ) on classes of (ψ,β)-differentiable functions defined on the real axis.